ANALISIS KREDIT BERMASALAH PT BANK RAKYAT INDONESIA (PERSERO) TBK DI MASA PANDEMI COVID 19 - Tommy Munaf; Rohmat Mahfuddin (EKONOMIKA, 2023)
This research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk. The purpose of this study was to identify and analyze non-performing loans at PT Bank Rakyat Indonesia (Persero) Tbk during the Covid 19 pandemic. This study aims to identify and analyze (1) the number of non-performing loans at PT Bank Rakyat Indonesia during the Covid 19 pandemic, (2) What policies did PT Bank Rakyat Indonesia implement in efforts to settle problem loans during the Covid 19 pandemic. The research method used is descriptive qualitative method. The type of data used is secondary data obtained from the financial statements of PT. Bank Rakyat Indonesia (Persero) Tbk in 2020-2021. The data analysis technique used is descriptive analysis technique. Based on the results of calculating the number of non-performing loans using the Non-Performing Loan ratio, the results show that PT. Bank Rakyat Indonesia (Persero) Tbk during the Covid 19 pandemic experienced an increase. The policy taken by PT Bank Rakyat Indonesia (Persero) Tbk in an effort to recover problem loans during the Covid 19 pandemic was by restructuring, especially in the UMKM segment.